Whole genome characterization of Torque teno sus virus 1 (TTSuV1) in wild and domestic pigs: insights into genetic classification, host differentiation, and intra-host variation - Li, Xiaolong; Tavares, Yasmin; Carneiro, Céline M.; Phillips, Caroline; Subramaniam, Kuttichantran; Lednicky, John; Boughton, Raoul K.; Pepin, Kim M.; Miller, Ryan S.; VerCauteren, Kurt C.; Wisely, Samantha M. (Frontiers in microbiology, 2025)
Torque teno sus virus 1 (TTSuV1), a member of the family, is highly prevalent in swine populations and exhibits substantial genetic diversity. Despite its ubiquity, TTSuV1 remains understudied, particularly regarding its genetic diversity, host-specific differentiation, and intra-host variation. These characteristics are critical for understanding its evolution, transmission dynamics, and potential applications in biosecurity monitoring. Field and laboratory protocols included capturing wild pigs, collecting whole blood samples, and screening for TTSuV1-positive samples through PCR. TOPO TA cloning was used to amplify individual viral variants within hosts, and whole genome sequencing (WGS) was performed on selected clones. A dated phylogenetic tree was reconstructed using TTSuV1 whole genome sequences obtained from wild pig samples in this study and all available sequences from NCBI. To evaluate genetic differentiation between wild and domestic pigs, partial viral sequences (~700 bp) were analyzed using phylogenetic D statistic and analysis of molecular variance (AMOVA). Intra-host variation was assessed by calculating pairwise identity percentages among viral clones from individual hosts and constructing haplotype networks. Phylogenetic analysis of whole genome sequences grouped TTSuV1 into four clades, with sequences from wild pigs distributed across all clades. Known subtypes 1a, 1b, and 1c were localized within Clades 3 and 4, leaving sequences in Clades 1 and 2 with unidentified subtypes. Partial sequence analysis revealed significant host-specific genetic differentiation: the D statistic confirmed a non-random association between host type (wild vs. domestic) and phylogeny, and AMOVA further showed contributions of both host type and geography to overall variation. Intra-host variation analysis provided evidence for multiple sources of genetic diversity within individual hosts. Pairwise identity percentages among viral clones ranged from 63.6% to 100%, with lower identity values indicating co-infection with distinct viral variants. Haplotype network analysis revealed mutational steps between haplotypes from the same host, suggesting that intra-host evolution also contributes to within-host genetic variation. This study highlights the significant genetic diversity and host-specific differentiation of TTSuV1, with wild pigs playing a key role in its evolution. Both intra-host evolution and co-infection contribute to its diversity, underscoring its potential as a tool for monitoring biosecurity risks and cross-transmission between wild and domestic pigs.